2009
DOI: 10.1158/1940-6207.capr-08-0211
|View full text |Cite
|
Sign up to set email alerts
|

ABT-510 Is an Effective Chemopreventive Agent in the Mouse 4-Nitroquinoline 1-Oxide Model of Oral Carcinogenesis

Abstract: Despite numerous advances, the 5-year survival rate for head and neck squamous cell cancer (HNSCC) has remained largely unchanged. This poor outcome is due to several variables, including the development of multiple primary tumors. Therefore, it is essential to supplement early detection with preventive strategies. Using the 4-nitroquinoline 1-oxide (4-NQO) mouse model, we sought to define an appropriate dose and duration of administration that would predict the histologic timeline of HNSCC progression. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 52 publications
(44 reference statements)
5
65
0
1
Order By: Relevance
“…Although several studies have targeted the VEGF family in ovarian cancer (15)(16)(17)(18), another effective approach for the treatment of various cancers are peptides derived from the TSR antiangiogenic domain of TSP-1 (19). Numerous studies have shown the antiangiogenic and antitumor effects of 3TSR (20)(21)(22) and ABT-510 (11,23,24) and have shown safety and efficacy in animal and human studies (12,13,25,26). We have previously evaluated ABT-510 in the treatment of EOC and reported decreased tumor burden as well as an increase in the uptake of the chemotherapy drugs cisplatin and paclitaxel through vascular normalization (8).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have targeted the VEGF family in ovarian cancer (15)(16)(17)(18), another effective approach for the treatment of various cancers are peptides derived from the TSR antiangiogenic domain of TSP-1 (19). Numerous studies have shown the antiangiogenic and antitumor effects of 3TSR (20)(21)(22) and ABT-510 (11,23,24) and have shown safety and efficacy in animal and human studies (12,13,25,26). We have previously evaluated ABT-510 in the treatment of EOC and reported decreased tumor burden as well as an increase in the uptake of the chemotherapy drugs cisplatin and paclitaxel through vascular normalization (8).…”
Section: Discussionmentioning
confidence: 99%
“…Candida infection in mice is characterized by fungal lesions, inflammation in the tongue, decreased food intake, weight loss and eventually a moribund state. Oral pathology resembles chronic candidal infection lesions, as well as epithelial dysplasia in mouse oral cancer models 12,18 .…”
Section: Introductionmentioning
confidence: 99%
“…This model helped reveal that a clinically relevant inhibitor of the mammalian target of rapamycin signaling pathway (rapamycin) represents a potential chemopreventive approach for halting progression in the oral cavity to HNSCC (10). Hasina et al (17) administered 4NQO at a dose of 100 μg/mL in drinking water to CBA mice for 8 weeks, which caused elevated incidences of hyperkeratoses, dysplasias, and SCCs in the oral cavity and minimal morbidity and mortality over a period of 32 weeks. In these mice, the use of an antiangiogenic agent, ABT-510, reduced the overall incidence of SCC in the oral cavity, supporting the further evaluation of angiogenesis inhibitors in HNSCC prevention.…”
mentioning
confidence: 99%
“…An emerging body of data suggests that the progressive changes occurring in oral tumoral lesions of the 4NQO mouse model reflect changes that occur in human HNSCC. These shared changes include altered expression of differentiation markers such as keratins, decreased expression or acquisition of potential inactivating mutations in tumor suppressor genes such as p16 and p53, increased expression of the epidermal growth factor receptor and cyclooxygenase-2, enhanced angiogenesis, increased levels of vascular endothelial growth factor, and increased activity of the phosphoinositide-3-kinase-Aktmammalian target of rapamycin pathway (9,10,17,31). Therefore, the in-depth analysis of 4NQO-induced premalignant and malignant lesions may provide a framework for future explorations of the earliest molecular events in HNSCC progression.…”
mentioning
confidence: 99%